Pengaruh Pembebanan Terhadap Waktu pada Kopling Dua kumulator sebagai Sumber Daya Listrik Cadangan - Cekmas Cekdin; Siti Sailah (Jurnal Rekayasa Mesin, 2021)
The use of accumulators so far as an energy source is only in an emergency situation and is limited by the time of use. The tool is called an Uninterruptible Power Supply (UPS). The way of  the tool works  is ineffective and unreliable, so there there needs to be a new innovation that can be used at any time and is not limited to the time of use. The results of the study present the coupling of two accumulators as a backup power source as an alternative provider of the main energy source that can provide a way out in the event of interference from PLN, and work for a relatively long time. Coupling of Two Accumulators as a backup power source begins with determining the characteristics of each component such as accumulators, inverters, rectifiers, current booster circuits, and voltage sensors. The next step is to determine the maximum loading for the system to work long enough. Furthermore, it is analyzed carefully and in a long time so that the design results is really suitable for use as a coupling of two accumulators as a reliable backup power source